2015
DOI: 10.4102/aej.v3i1.166
|View full text |Cite
|
Sign up to set email alerts
|

Special edition of African Evaluation Journal on the national evaluation system

Abstract: No abstract available.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…This has meant that many of the systems have prioritised monitoring rather than evaluations. For example, just under a decade ago, research showed that although 89% of government departments in South Africa had an M&E unit, the focus was on tracking outputs at an operational level and not on learning (Goldman et al 2015;Porter & Goldman 2013).…”
Section: Current Approaches To Building National Monitoring and Evalu...mentioning
confidence: 99%
“…This has meant that many of the systems have prioritised monitoring rather than evaluations. For example, just under a decade ago, research showed that although 89% of government departments in South Africa had an M&E unit, the focus was on tracking outputs at an operational level and not on learning (Goldman et al 2015;Porter & Goldman 2013).…”
Section: Current Approaches To Building National Monitoring and Evalu...mentioning
confidence: 99%
“…National governments in the region have been evolving over the past few decades in developing NESs to help track performance in the implementation of national development plans (Basheka & Byamugisha 2015;Goldman, Rabie & Abrahams 2015). This practice is only beginning to emerge at the subnational level and is still largely focused on trying to put monitoring systems in place.…”
Section: Introductionmentioning
confidence: 99%